ANALISA PENDIDIKAN PESANTREN DAN PERANNYA TERHADAP PENDIDIKAN ISLAM - Fathul Amin (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2019)
Pesantren is a unique educational institution. Not only because of its very long existence, but also because of the culture, methods, and networks applied by the institution. Therefore, many studies have been conducted from different perspectives, especially in the terms of periodization of its history. However, the study appears to be so broad and described in general while correlating with the role and its progress involved. On this basis, this research report will examine deeper in the role of pesantren education in the context of Islamic education. This present study aims at identifying the role of Islamic boarding schools as Islamic educational Institution. This study employs a qualitative approach and literature study method. Based on the results of the study, Islamic boarding schools in fact provides the process of teaching, educating, developing, and spreading the religion of Islam. In relation to the objectives of Islamic boarding schools, it in principle aims to develop Islamic personality, specifically the personality that put more concern on the believing and consciousness of Allah, noble character, piety, usefulness and loyalty to the community, and being a custodian of all humankinds (khadim al-ummaħ).